2023
DOI: 10.1038/s42004-023-00942-1
|View full text |Cite
|
Sign up to set email alerts
|

Order–order assembly transition-driven polyamines detection based on iron−sulfur complexes

Abstract: Innovative modes of response can greatly push forward chemical sensing processes and subsequently improve sensing performance. Classical chemical sensing modes seldom involve the transition of a delicate molecular assembly during the response. Here, we display a sensing mode for polyamine detection based on an order–order transition of iron–sulfur complexes upon their assembly. Strong validation proves that the unique order–order transition of the assemblies is the driving force of the response, in which the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…In this context, the biogenic polyamine content in humans is considered an essential biomarker for different types of cancers. , For instance, Giskeødegård et al demonstrated that metabolic profiling of spermine could be a promising diagnostic tool to assess the aggressiveness of prostate cancer. Hence, polyamine detection and quantification in physiological fluids are crucial for the timely diagnosis and prognosis of human malignancies . Fluorescence imaging or signaling is the most commonly employed method for detecting polyamines. However, it is invasive and complex and is not deliverable.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this context, the biogenic polyamine content in humans is considered an essential biomarker for different types of cancers. , For instance, Giskeødegård et al demonstrated that metabolic profiling of spermine could be a promising diagnostic tool to assess the aggressiveness of prostate cancer. Hence, polyamine detection and quantification in physiological fluids are crucial for the timely diagnosis and prognosis of human malignancies . Fluorescence imaging or signaling is the most commonly employed method for detecting polyamines. However, it is invasive and complex and is not deliverable.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, polyamine detection and quantification in physiological fluids are crucial for the timely diagnosis and prognosis of human malignancies. 10 Fluorescence imaging or signaling is the most commonly employed method for detecting poly-amines. 11−13 However, it is invasive and complex and is not deliverable.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation